A new Denisiella Folsom and Mills, 1938 (Collembola: Sminthurididae) from Colombia - Ospina, M.; Palacios Vargas, JG (2009)
Denisiella colombiana sp. nov. is described and illustrated from Colombia. Males and females are studied. Two keys for the species of the world are included, one for males and one for females.